Evaluating sperm quality characteristics obtained through the female teaser method in native chicken breeds - Udrayana, Setya Budhi; Kasianto, Kasianto; Iswati, Iswati; Bintari, Intan Galuh (Livestock and Animal Research, 2023)
Objective: The quality and quantity of chicken sperm are critical factors influenced by the semen collection method. Therefore, this study aims to evaluate the sperm quality obtained from three native chicken breeds using the female teaser method.Methods: These three native chicken breeds are Arabic, Birma, and Kampung Unggul Balitbangtan (KUB) chickens. Each breed comprised a group of three roosters, and the semen collection was performed ten times. Macroscopic and microscopic evaluations were conducted to assess the chicken sperm. The collected data were analyzed using Analysis of Variance (ANOVA) followed by Duncan's multiple range test (DMRT).Result: The results of this study showed significant differences (P<0.05) in the sperm volume among the chicken breeds, with Birma (0.51 ml) and KUB chickens (0.60 ml) exhibiting distinct volumes compared to Arabic chicken (0.25 ml). Generally, the chicken sperm exhibited a milky white color and thick consistency. Microscopic evaluation yielded a mass motility rating of 3+. Meanwhile, individual motility and viability did not exhibit significant differences (P>0.05) among the three native chicken breeds. Abnormalities displayed significant variations (P<0.05), with Birma chicken showing the highest abnormality rate at 9.77%± 0.28. Sperm concentration did not exhibit significant differences (P>0.05), with the highest concentration observed in Arabic chicken at 4265.33±59.84 (x106 cells/ml). However, total sperm count and total motile sperm count exhibited significant variations (P<0.05), with the highest values recorded in KUB chicken at 2241.82±264.13 (x106 cells) and 1936.27±169.85 (x106 cells), respectively.Conclusions: In conclusion, the semen collection method using the female teaser yielded native chicken sperm with high quality and quantity and meets the required standards for successful insemination. This method holds potential and is recommended for application in native chicken breeding programs.